Enhancing Interest and Creativity in Akidah Akhlak Learning through Animated Videos - Sumarno, Sumarno; Muchtar, Asmaji; Makhshun, Toha (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study examines the implementation of animated video media in Akidah Akhlak learning and its effect on enhancing students’ interest and creativity at MTs Arrohmah. The research responds to the growing demand for engaging, relevant digital media in the modern classroom to improve instructional quality and foster moral character. Using a qualitative descriptive method, data were collected from students and teachers through observation, interviews, and documentation. Findings reveal that animated videos improved students’ attention, enthusiasm, and independent learning, while stimulating creative thinking and idea generation. They also simplified the understanding of abstract Akidah Akhlak concepts and promoted interactive, dynamic classroom engagement. Unlike previous studies that predominantly applied animated media in science or language learning, this research uniquely focuses on its integration into Islamic moral education at the madrasah level. This approach contributes an innovative and practical framework for leveraging digital animation to boost interest and creativity in religious education, supporting more meaningful and enjoyable learning in the digital era.